A criança em Luis Fernando Verissimo - Moraes, Cintia da Silva (2023)
This work analyzes, in the light of studies on humor, the presence of children in texts by Luis Fernando Verissimo. It is justified by the author's literary relevance within the scope of Brazilian literature and the lack of research with this thematic focus. The corpus consists of ten selected texts from the author's extensive work, which there is the child’s presence as the central character, predominantly in direct speech: “Cornita” (1983), “Peça infantil” (1984), “Sexa” (1985), “A conversa” (1987), “O pleito” (1990), “O diamante” (1990), “O 'flete'” (1990), “Relógio Digital” (1990), “Festa de criança” ( 1991) and “Festa de Aniversário” (1999). Through the analysis of this set of texts, it was sought to confirm the following hypothesis: the perspective adopted by the author elevates the figure of the child while satirizes the adult in an authoritarian stance. Children are articulate, they talk to each other and to adults, they argue, they express their desires and, sometimes, they disarticulate the adults' arguments. We realized that Verissimo recognizes the child as an integral human being on its emotional, intellectual, psychological and social development phase: childhood. Therefore, subject who has civil, human and social rights guaranteed by law. Among the fundamental texts for the research, we highlight Manuel Pinto (1997), Mary Del Priore (2000) and Philippe Ariès (2006 [1978]), regarding the concept of child and childhood, and Vladimir Propp (1992), Victor Raskin (1985) and Luiz Carlos Travaglia (1990, 2015), for the issues related to humor.